Analysis of Affixation Errors in the Comment Section of AM Youtube Channel - Afria, Rengki (Southeast Asian Language and Literature Studies, 2025)
The purpose of this study is to describe the forms of affixation errors and the factors that cause these errors in the comments section on the AM YouTube channel. This study employs a descriptive qualitative method. The data are obtained from four selected videos on the AM YouTube channel that representatively reflect various comment patterns made by users. The data were collected by identifying and classifying incorrect uses of affixation found in the comments section. The results of the study show that the misapplication of affixes includes: (a) omission of affixes, where prefixes such as meN-, se-, and confixes meN-kan, meN-i are frequently omitted; and (b) writing errors, which commonly involve prefixes ter-, meN-, ber-, suffixes -an, -kan, and confixes pe-an, se-nya, and meN-kan. No errors were found in infixes. Furthermore, the factors causing these errors are identified as language user factors, environmental factors, and language-related factors.